The Effect of Honey Concentration on The Physicochemical and sensory Characteristics of Nutmeg Velva (Myristica fragrans Houtt - Sophia Grace Sipahelut; Anugrah Ariq Amanulloh; Vita Novalin Lawalata (Jurnal Sains dan Teknologi Pangan, 2023)
The development of nutmeg flesh into Velva products is an effort to increase the economic value of nutmeg flesh. The choice of honey to replace granulated sugar in making velva as a low-calorie sweetener and has functional value. The aim of this research was to determine the effect of adding honey on the physicochemical and sensory characteristics of nutmeg velva. The research design used was a completely randomized design with one factor, namely honey concentration with three treatment levels, namely: 30%, 40%, 50%. The parameters observed include total sugar content, water content, pH, total dissolved solids, sensory tests including aroma, color, texture and taste. The results showed that the addition of honey with different concentrations had a real influence on the physicochemical and sensory characteristics of velva nutmeg. The higher the honey concentration, the total sugar content, pH and total dissolved solids of the nutmeg velva increases, but the water content of the velva decreases. The physicochemical characteristics of the nutmeg velva produced include: total sugar content 18.20% - 20.25%, water content 77.04% - 80.56%, pH 3.65 - 3.84, total dissolved solids 22.33 – 26.53 °Brix. Meanwhile, the sensory characteristics include: aroma 5.03 – 6.03 (slight nutmeg velva aroma to nutmeg aroma), color 4.43 – 5.33 (light brown to brown), texture 5.83 – 6.43 (Velva nutmeg texture is close to soft to soft), and taste 10 – 5.83 (ordinary taste to sweet taste).